Pattern and hotspots analysis of forest fires in district Tehri of Garhwal Himalayan Region, Uttarakhand - Sana Rafi; Ashutosh Singh; Mahendra Singh; Abhishta Adhikary (National Geographical Journal of India, 2025)
The Uttarakhand State is rich in forest resources, and according to the India State of Forest Report 2023, the State has a total 71.05% forest cover area out of the total geographical area. But, at present, various anthropogenic and natural factors are affecting and degrading the wealth and health of forest resources. One of the important factors responsible for forest resource degradation is forest fire. Therefore, the present study aims to understand the forest fire pattern and trends and their hotspots in the study area. For this purpose, primary and secondary data have been used and processed in the SPSS software for statistical analysis and in GIS environment to prepare the spatial distribution maps. The study reveals that during the study period, total 135 forest fire incidents have been reported in the study area with a total 530 hours of forest fire duration which has affected 123 hectares of forest cover area. During the study period, in the study area, the average monthly forest fire incident is 45 (SD ± 21.6), which varies from 27 as the minimum in April and 69 as the maximum in May; the average monthly forest fire duration is 176 hours (SD ± 64.7) which varies from 103 hours as the minimum in the month of April and 223 hours as the maximum in the month of May; and the mean monthly forest fire affected area in district Tehri is 41 hectares (SD ± 23.1) which varies from 17 hectares as the minimum in the month of April and 63 hectares as the maximum in the month of May. The study found a strong relation between the number of fires, how long they lasted, and the area affected. The study area is divided into five forest ranges out of which the Tehri is the most forest fire affected ranges and the Balganga is the least forest fire affected range. Three major fire hotspots were identified, especially in the central part of the study area, with high confidence. The study also shows that besides anthropogenic factors, the biological factors, e.g., the accumulation of pine (Chir) needles on the surface work as a fuel to forest fires and the physical factors, e.g., topography, climatic conditions, moisture etc. are spread the fire. Thus, this study recommends pre-forest fire control measures such as removing of pine needles from human activity areas, plantation of fire adaptive plant species and making of fire lines.